Cell Cycle Deficits in Neurodegenerative Disorders: Uncovering Molecular Mechanisms to Drive Innovative Therapeutic Development - Joseph, Chitra; Mangani, Abubakar Siddiq; Gupta, Veer; Chitranshi, Nitin; Shen, Ting; Dheer, Yogita; KB, Devaraj; Mirzaei, Mehdi; You, Yuyi; Graham, Stuart L; Gupta, Vivek (Aging and disease, 2020)
Cell cycle dysregulation has been implicated in the pathogenesis of neurodegenerative disorders. Specialised function obligates neuronal cells to subsist in a quiescent state of cell cycle once differentiated and therefore the circumstances and mechanisms underlying aberrant cell cycle activation in post-mitotic neurons in physiological and disease conditions remains an intriguing area of research. There is a strict requirement of concurrence to cell cycle regulation for neurons to ensure intracellular biochemical conformity as well as interrelationship with other cells within neural tissues. This review deliberates on various mechanisms underlying cell cycle regulation in neuronal cells and underscores potential implications of their non-compliance in neural pathology. Recent research suggests that successful duplication of genetic material without subsequent induction of mitosis induces inherent molecular flaws that eventually assert as apoptotic changes. The consequences of anomalous cell cycle activation and subsequent apoptosis are demonstrated by the increased presence of molecular stress response and apoptotic markers. This review delineates cell cycle events under normal physiological conditions and deficits amalgamated by alterations in protein levels and signalling pathways associated with cell-division are analysed. Cell cycle regulators essentially, cyclins, CDKs, cip/kip family of inhibitors, caspases, bax and p53 have been identified to be involved in impaired cell cycle regulation and associated with neural pathology. The pharmacological modulators of cell cycle that are shown to impart protection in various animal models of neurological deficits are summarised. Greater understanding of the molecular mechanisms that are indispensable to cell cycle regulation in neurons in health and disease conditions will facilitate targeted drug development for neuroprotection. Key words: Cell cycle, Apoptosis, Neuron, Neurodegeneration, CDK, Cyclin